2020
DOI: 10.33145/2304-8336-2020-25-478-489
|View full text |Cite
|
Sign up to set email alerts
|

ORAL HYGIENE IN CHILDREN WITH DISTURBANCES IN TOOTH FORMATION WHO WERE AFFECTED AS A CONSEQUENCE OF THE ChNPP ACCIDENT

Abstract: Objective. evaluation of oral hygiene to enhance the prophylaxis of complications specifically of dental caries in children with disturbances in tooth formation (DTF) who live on radiologically contaminated territories after the Chornobyl NPP (ChNPP) accident. Materials and methods. Children aged 6–14 years (n = 1470) with DTF were the study subjects examined in 2012– 2016. Among them there were (n = 528) residents of the zones III and IV of radiological contamination after the ChNPP accident with 137Cs soil c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Diseases of the oral mucosa of both adult and children's populations occupy an important place in dental practice [107][108][109][110]. Clinical studies show that pathological changes in the oral mucosa are often manifestations of infectious diseases, allergic conditions, and consequence of disorders in the work of various organs and systems in children with concomitant pathology [111][112][113][114][115][116][117][118][119][120]. In such cases, the establishment of a final diagnosis requires consultations with doctors of various specialties, and additional research methods [121][122][123][124][125][126][127].…”
Section: Laboratory Methods Of Research In the Diagnosis Of Oral Muco...mentioning
confidence: 99%
“…Diseases of the oral mucosa of both adult and children's populations occupy an important place in dental practice [107][108][109][110]. Clinical studies show that pathological changes in the oral mucosa are often manifestations of infectious diseases, allergic conditions, and consequence of disorders in the work of various organs and systems in children with concomitant pathology [111][112][113][114][115][116][117][118][119][120]. In such cases, the establishment of a final diagnosis requires consultations with doctors of various specialties, and additional research methods [121][122][123][124][125][126][127].…”
Section: Laboratory Methods Of Research In the Diagnosis Of Oral Muco...mentioning
confidence: 99%
“…In addition, the authors noted an increased incidence of aphthous stomatitis and recurrent herpes in the exposed population. [2] The work of other researchers noted an increase in the incidence of periodontal diseases in the population of Belarus, especially in areas affected by the Chernobyl accident. [3] In the region of the Semipalatinsk nuclear test site, dental morbidity in children and adults was also studied.…”
Section: Short Communicationmentioning
confidence: 97%
“…[2] The work of other researchers noted an increase in the incidence of periodontal diseases in the population of Belarus, especially in areas affected by the Chernobyl accident. [3] In the region of the Semipalatinsk nuclear test site, dental morbidity in children and adults was also studied. The most extensive comprehensive examination of the affected population of the Semipalatinsk region with the study of the course, treatment and prevention of periodontal and oral mucosa diseases is given, where it is convincingly shown that in the mechanism of development of oral mucosa candidiasis and chronic recurrent aphthous stomatitis, the leading role belongs to changes in immune parameters, salivary dysfunction and microcirculation disorders.…”
Section: Short Communicationmentioning
confidence: 97%
“…Адже лікар підвищує свою кваліфікацію все життя й непомітно для себе і для оточуючих його колег змінюється і як людина. Особливо важливі дружні доброзичливі стосунки між колегами у робочих колективах медичних працівників, які кожен день стикаються з нестандартними ситуаціями, в тому числі з наданням невідкладної допомоги пацієнтам, тощо [4][5][6][7][8][9][10][11][12].…”
unclassified